Search for resonant WW and WZ production in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (American Physical Society (APS), 2011)
We search for resonant WW or WZ production by using up to 5.4fb -1 of integrated luminosity collected by the D0 experiment in runB II of the Fermilab Tevatron Collider. The data are consistent with the standard model background expectation, and we set limits on a resonance mass by using the sequential standard model W′ boson and the Randall-Sundrum model graviton G as benchmarks. We exclude a sequential standard model W ′ boson in the mass range 180-690GeV and a Randall-Sundrum graviton in the range 300-754GeV at 95% C.L.